Biodegradable poly (lactic acid)-poly (ε-caprolactone)-nanolignin composite films with excellent flexibility and UV barrier performance. (December 2020) - Yang, Weijun; Qi, Guochuang; Ding, Hui; Xu, Pengwu; Dong, Weifu; Zhu, Xiangmiao; Zheng, Ting; Ma, Piming
Abstract: In this work, poly(lactide- ε -caprolactone) copolymer grafted lignin nanoparticles (LNP-g-P(LA-CL) were synthesized, through a ring-open polymerization (ROP) of L-lactide and ε -caprolactone, initiated from the hydroxyl groups on LNP surface. Then PLA, PCL and various amounts of the copolymer were blended via a facile solvent casting approach. Mechanical tests showed that the addition of 6 wt% LNP-g-P(LA-CL) copolymer made a significant contribution to the toughness of PLA/PCL blend, which was enhanced by 4 folds in comparison with neat PLA. Meanwhile, the crystallization ability of both PLA and PCL were improved due to the better interfacial adhesion and mobility of PLA and PCL chains. Well-distributed elongated-fibrils and crazes, observed after tensile measurements for the nanocomposites, were responsible for absorbed energy, improved toughness and flexibility of PLA. Furthermore, UV–Vis spectroscopy measurements showed that the incorporation of 12 wt% of LNP-g-P(LA-CL) copolymer make PLA/PCL film able to shield almost 100 wt% of UV-B and UV-C irradiation. PLA/PCL-LNP nanocomposites can be used as impact resistance materials and in UV-resistance fields, such as sunshade and food packaging areas. Highlights: Lignin nanoparticles grafting poly(lactide- ε -caprolactone) copolymer was synthesized. LNP-g-P(LA-CL) copolymer contributed to 4 folds of toughness of PLA/PCL blend in comparison with PLA. The crystallinity of PLA/PCL-12L were enhanced from 29.4% to 41.3% due to the improved mobility. The cavitation and fibrillation effects could well explain the toughing mechanism. Incorporation of LNP-g-P(LA-CL) copolymer make PLA/PCL film shield 100% of UV-B/C irradiation.